(3GdeMQQ aj GdCMcGes - (3eMeO Hf CMeO YHO GdgGOjs ((3GHQGgje Hf QGTO GdMfHdi s)
(3ChdgG (B:s
(3CeG HYO agPG oeNJUQ jTJed Ydi LedI ef GdCMGOjK GdfHhjI aj GdCMcGe GdTQYjI GfJNHJg ef cJH GdCFeI GdeTghQjf s
(3BNQgG (B:s
(3hYf YGFTI bGdJ cGf QShd Gddg Udi Gddg Ydjg hSde (B"(3EPG eQV CMO ef Cgdg faK Ydjg HGdeYhPGJ Je cJGH GdeMQQ s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3oefJNH s
Keywords: (3GdMOjK h GdeUWdMs